BSADP mid term implementation report, volume 6 : external review - Bauchi State Agricultural Development Programme (Bauchi State : Bauchi State ADP, 1984)
This report presents the findings of the external review consultant who examined BSADP's activities within the wider environment of agricultural development policy in Nigeria, specifically the food production plan, and focuses on the design of the organisation which was created to achieve programme goals.
Includes bibliographical footnotes.
ne 19/08/2021
Ref.
Keywords: Agricultural economics; Nigeria